Rational design of metal nitride redox materials for solar-driven ammonia synthesis - Michalsky, Ronald; Pfromm, Peter H.; Steinfeld, Aldo (My University, 2015)
Fixed nitrogen is an essential chemical building block for plant and animal protein, which makes ammonia (NH3) a central component of synthetic fertilizer for the global production of food and biofuels. A global project on artificial photosynthesis may foster the development of production technologies for renewable NH3 fertilizer, hydrogen carrier and combustion fuel. This article presents an alternative path for the production of NH3 from nitrogen, water, and solar energy. The process is based on a thermochemical redox cycle driven by concentrated solar process heat at 700-1200°C that yields NH3 via the oxidation of a metal nitride with water. The metal nitride is recycled via solar-driven reduction of the oxidized redox material with nitrogen at atmospheric pressure. We employ electronic structure theory for the rational high-throughput design of novel metal nitride redox materials and to show how transition-metal doping controls the formation and consumption of nitrogen vacancies in metal nitrides. We confirm experimentally that iron doping of manganese nitride increases the concentration of nitrogen vacancies compared to no doping. The experiments are rationalized through the average energy of the dopant d-states, a descriptor for the theory-based design of advanced metal nitride redox materials to produce sustainable solar thermochemical ammonia.
Keywords: Concentrated solar energy; Thermochemical redox cycle; Metal nitride; Hydrogen storage; Haber Bosch; Density functional theory